2015
DOI: 10.1002/ange.201508506
|View full text |Cite
|
Sign up to set email alerts
|

In‐Membrane Chemical Modification (IMCM) for Site‐Specific Chromophore Labeling of GPCRs

Abstract: We present in-membrane chemical modification (IMCM) for obtaining selective chromophore labeling of intracellular surface cysteines in G-protein-coupled receptors (GPCRs) with minimal mutagenesis.T his method takes advantage of the natural protection of most cysteines by the membrane environment. Practical use of IMCM is illustrated with the site-specific introduction of chromophores for NMR and fluorescence spectroscopyinthe human k-opioid receptor (KOR) and the human A 2A adenosine receptor (A 2A AR). IMCM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…S1A). To achieve specific labeling of the two genetically introduced cysteines, but spare the transmembrane native cysteines, we labeled the receptors in isolated cell membranes, as described previously 49 . After labeling, the receptors were purified and reconstituted in MSP1D1 nanodiscs, which can accommodate only a single monomeric receptor per nanodisc 50 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1A). To achieve specific labeling of the two genetically introduced cysteines, but spare the transmembrane native cysteines, we labeled the receptors in isolated cell membranes, as described previously 49 . After labeling, the receptors were purified and reconstituted in MSP1D1 nanodiscs, which can accommodate only a single monomeric receptor per nanodisc 50 .…”
Section: Resultsmentioning
confidence: 99%
“…(2) To minimize the effect of fluorophores on the receptor’s dynamics we used small organic dyes attached to strategically engineered cysteines. (3) We avoided the need to remove native cysteines and associated to that potential structural perturbations by using the previously developed in-membrane labeling procedure 49 . We showed that the mutant form of the receptor retains functional activity using the thermal shift assay and cAMP signaling assay in live HEK293T cells.…”
Section: Discussionmentioning
confidence: 99%
“…19 F-labeled H 1 R was prepared using the in-membrane chemical modification protocol [ 25 ]. Subsequent purification steps followed the above described protocol used for producing u- 15 N H 1 R.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were concentrated to 280 µL in a Vivaspin-6 concentrator with a 30 kDa MWCO (Sartorius, Goettingen, Germany), 20 µL D 2 O was added and the sample was transferred to 5 mm Shigemi NMR tube. 19 F-labeled H 1 R was prepared using the in-membrane chemical modification protocol [25]. Subsequent purification steps followed the above described protocol used for producing u- 15 N H 1 R.…”
Section: H 1 R Production and Purification For Nmr Experimentsmentioning
confidence: 99%
See 1 more Smart Citation